2011
DOI: 10.1016/j.jmaa.2010.10.058
|View full text |Cite
|
Sign up to set email alerts
|

The e-support function of an e-convex set and conjugacy for e-convex functions

Abstract: A subset of a locally convex space is called e-convex if it is the intersection of a family of open halfspaces. An extended real-valued function on such a space is called e-convex if its epigraph is e-convex. In this paper we introduce a suitable support function for e-convex sets as well as a conjugation scheme for e-convex functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 4 publications
0
44
0
Order By: Relevance
“…Based on the generalized convex conjugation theory introduced by Moreau [16], a suitable conjugation scheme is provided in [15] for e-convex functions. Consider the set W := X X R with the coupling functions c : X W !…”
Section: Is a Proper E-convex Function If And Only Ifmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the generalized convex conjugation theory introduced by Moreau [16], a suitable conjugation scheme is provided in [15] for e-convex functions. Consider the set W := X X R with the coupling functions c : X W !…”
Section: Is a Proper E-convex Function If And Only Ifmentioning
confidence: 99%
“…c(x; (x ; y ; )) 2 R, with (x ; y ; ) 2 W and 2 R are called c-elementary; in the same way, c 0 -elementary functions are those of the form (x ; y ; ) 2 W ! c(x; (x ; y ; )) 2 R, with x 2 X and 2 R. In [15] it is shown that the family of the proper e-convex functions from X to R along with the function identically equal to 1 is actually the family of pointwise suprema of sets of celementary functions. Using an analogous terminology, a function g : W !…”
Section: Is a Proper E-convex Function If And Only Ifmentioning
confidence: 99%
“…For a function h : X → R we denote Δh := eco(dom h) ⊂ X, a set of crucial importance as observed in [11,15]. …”
Section: It Holds That Epi(co H) = Co(epi H) H γ ≤ Co H ≤ Co H ≤ H Amentioning
confidence: 99%
“…Recently, a Moreau generalized conjugacy related to evenly convex functions has been introduced in [11]. Another approach, using evenly quasiconvex duality and the conjugacy machinery (see [9,14,18], for instance), is given in [19].…”
Section: Evenly Convex Conjugacy In General Topological Vector Spacesmentioning
confidence: 99%
See 1 more Smart Citation